2004
DOI: 10.2134/jeq2004.1144
|View full text |Cite
|
Sign up to set email alerts
|

Denitrification Enzyme Activity of Fringe Salt Marshes in New England (USA)

Abstract: Coastal salt marshes are a buffer between the uplands and adjacent coastal waters in New England (USA). With increasing N loads from developed watersheds, salt marshes could play an important role in the water quality maintenance of coastal waters. In this study we examined seasonal relationships between denitrification enzyme activity (DEA) in salt marshes of Narragansett Bay, Rhode Island, and watershed N loadings, land use, and terrestrial hydric soils. In a manipulative experiment, the effect of nutrient e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 41 publications
3
24
0
Order By: Relevance
“…Although denitriWcation rates measured in intact cores showed no fertilization eVects, denitriWcation enzyme activity measured in soil slurries from these same plots in June in a concurrent study showed signiWcantly elevated rates in the N treatments (Wigand et al 2004b). This suggests that with suYcient nitrate and labile organic matter, added nitrogen enhances denitriWcation rates.…”
Section: Discussionmentioning
confidence: 86%
“…Although denitriWcation rates measured in intact cores showed no fertilization eVects, denitriWcation enzyme activity measured in soil slurries from these same plots in June in a concurrent study showed signiWcantly elevated rates in the N treatments (Wigand et al 2004b). This suggests that with suYcient nitrate and labile organic matter, added nitrogen enhances denitriWcation rates.…”
Section: Discussionmentioning
confidence: 86%
“…Laboratory methodologies for the analysis of sediment and pore water samples are described in detail in Heitmuller (2007). Other samples and measurements, including surface water salinity, conductivity, temperature, and pH and leave tissue samples for plant C:N:P and stable N isotope ratios (Wigand et al 2004), are collected within the Tier 2 AA.…”
Section: Assessment Methodologymentioning
confidence: 99%
“…Amendment rates were 0.64 mgÁg À1 for C, 0.19 mgÁg À1 for N and 0.019 mgÁg À1 for P, based on fertilization levels in similar published experiments (Groffman et al 1996, Hunter and Faulkner 2001, Allen and Schlesinger 2004, Wigand et al 2004) and a molar C:N:P ratio of 46:7:1 for bacteria (Reiners 1986). One subset was incubated for 4 d and analyzed for CO 2 and CH 4 (GC-14 Gas Chromatograph, Shimadzu Scientific Instruments); another subset was incubated for 2 h and analyzed for N 2 O (GC-14 Gas Chromatograph, Shimadzu Scientific Instruments).…”
Section: Nutrient Limitationmentioning
confidence: 96%